2020
DOI: 10.1093/jat/bkaa198
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Non-Alcoholic Food-Derived Ethanol and Methanol Exposure in Humans

Abstract: Food-derived alcohol is almost not in question due to its low concentration. Nevertheless, could it pose a problem for some risk groups and forensic cases? To answer this, we aimed to simultaneously evaluate ethanol and methanol ingredients of a variety of non-alcoholic foods in two different countries and estimate their possible health and forensic consequences. Alcohols in foods were analyzed by headspace gas chromatography. Human average acute daily food consumptions and food-derived blood alcohol concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Estimates from food derivatives show ethanol and methanol in humans at 7.9 mg/kg in beans, lentils, and peas (National Toxicology Program, 2003). However, Gürler et al (2022) found that the methanol content was 150 mg/kg for vegetables such as tomatoes, eggplant, and pickles and 130-390 mg/kg for legumes, such as beans, maize, and peas. These high levels might be due to food processing.…”
Section: Identification Of the Compounds Present In The Sample By Gc/msmentioning
confidence: 99%
“…Estimates from food derivatives show ethanol and methanol in humans at 7.9 mg/kg in beans, lentils, and peas (National Toxicology Program, 2003). However, Gürler et al (2022) found that the methanol content was 150 mg/kg for vegetables such as tomatoes, eggplant, and pickles and 130-390 mg/kg for legumes, such as beans, maize, and peas. These high levels might be due to food processing.…”
Section: Identification Of the Compounds Present In The Sample By Gc/msmentioning
confidence: 99%
“…Its consumption can lead to neurodegeneration and exert a paralytic effect on the blood vessels. The inadvertent consumption of methanol or beverages containing excessive amounts of methanol can result in blindness, liver disease, and even death [1,2]. Countries worldwide have strict regulations on the methanol content in alcoholic beverages [3].…”
Section: Introductionmentioning
confidence: 99%